Working Together to Improve Accessibility: Consortial E-Resource Accessibility and Advocacy. Issue 2 (2nd April 2020) - Pionke, JJ; Schroeder, H. M.
Abstract: In 2015, the Big Ten Academic Alliance (BTAA) Libraries formed the BTAA Library E-Resource Accessibility Group. This group, which consists of members from each Big Ten library and the BTAA Library Initiatives staff, was charged with creating boilerplate accessibility license language for vendor contracts, as well as collectively funding high level accessibility testing of e-resources and posting these publicly for all libraries and users. Since the creation of the group, about 50 databases have been tested and accessibility license language has been created that can be used and adapted by anyone. In 2019, the group welcomed another consortia, the Association of Southeastern Research Libraries (ASERL), to be partners in this work, renaming themselves the Library Accessibility Alliance. This paper examines the mission, accomplishments, and new partnership in more depth while also discussing the need for focused efforts to help ensure accessible e-resources.